1998
DOI: 10.1063/1.368884
|View full text |Cite
|
Sign up to set email alerts
|

ON-state reliability of amorphous-silicon antifuses

Abstract: The ON state of metal-to-metal amorphous-silicon antifuses suffers from two reliability concerns: switch-off and dc-stress failure. The switch-off current and dc-stress lifetime are strongly dependent on the temperature of the conducting filament and hence, on the programming current and ambient temperature. Numerical simulations of the filament temperature in the ON state were carried out to explain the experimental characteristics obtained in this work such as the dependence of the switch off and dc-stress f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The temperature in the antifuse under a given set of programming conditions is obtained by solving the heat equation. Then, the maximum temperature at the edges of the via at a given applied voltage is given by [4] where T amb is the ambient temperature, the thermal conductivity of amorphous silicon, a the radius of the via, i a constant, and J n (x) the Bessel function of the first kind of order n. The constant i is determined to be the root of the transcendental equation J 0 (a) ϭ 0 [5] From Fig. 1, the above equation can be reduced to T max ϭ 1.29206 ϫ 10 Ϫ6 V af exp(1.98945V af ) ϩ T amb [6] This steady-state temperature value is calculated for various values of the applied voltage.…”
Section: Thermal Model and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature in the antifuse under a given set of programming conditions is obtained by solving the heat equation. Then, the maximum temperature at the edges of the via at a given applied voltage is given by [4] where T amb is the ambient temperature, the thermal conductivity of amorphous silicon, a the radius of the via, i a constant, and J n (x) the Bessel function of the first kind of order n. The constant i is determined to be the root of the transcendental equation J 0 (a) ϭ 0 [5] From Fig. 1, the above equation can be reduced to T max ϭ 1.29206 ϫ 10 Ϫ6 V af exp(1.98945V af ) ϩ T amb [6] This steady-state temperature value is calculated for various values of the applied voltage.…”
Section: Thermal Model and Discussionmentioning
confidence: 99%
“…[1][2][3] We have previously reported on the energy considerations during the growth of a molten filament in metalto-metal amorphous-silicon antifuses, 4 and on the ON-state reliability of amorphous-silicon antifuses. 5 In this paper, we present a thermal model for the initiation of programming in these antifuses.The antifuses studied in this work are located in the via between two metal layers. The bottom metal electrode is Al-Si-Cu/TiW and the top metal electrode is Ti/TiW/Al-Si-Cu.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the existing metal-to-metal antifuses show very good off-state reliability; however, their on-state reliability is still an area of concern [19]. It was found that an amorphous silicon antifuse, once programmed, can switch back to the off-state during later operation.…”
Section: Introductionmentioning
confidence: 99%
“…It can induce the read disturb: the R ON increase of programmed antifuse cells to an off-state resistance (R OFF ) level during read operation. In the case of metal-insulator-metal (MIM) antifuse cells, read disturb problems have already been reported [5,6]. On the other hand, in the case of standard CMOS antifuse cells, few research results on read disturb problems have been reported yet.…”
Section: Introductionmentioning
confidence: 99%